Genetic landscape of adult Langerhans cell histiocytosis with lung involvement. Issue 2 (27th February 2020) - Jouenne, Fanélie; Chevret, Sylvie; Bugnet, Emmanuelle; Clappier, Emmanuelle; Lorillon, Gwenaël; Meignin, Véronique; Sadoux, Aurélie; Cohen, Shannon; Haziot, Alain; How-Kit, Alexandre; Kannengiesser, Caroline; Lebbé, Céleste; et al.
The clinical significance of the BRAF V600E mutation in adult Langerhans cell histiocytosis (LCH), including pulmonary Langerhans cell histiocytosis (PLCH), is not well understood. Similarly, the spectrum of molecular alterations involved in adult LCH has not been fully delineated. To address these issues, we genotyped a large number of adult LCH biopsies and searched for an association of identified molecular alterations with clinical presentation and disease outcome. Biopsies from 117 adult LCH patients, 83 with PLCH (median age 36.4 years, 56 females, 38 multisystem disease, 79 single system disease, 65 current smokers) were genotyped for the BRAF V600E mutation. In 69 cases, LCH lesions were also genotyped by whole-exome sequencing (WES) or targeted gene panel next-generation sequencing (NGS). Cox models were used to estimate the association of baseline characteristics with the hazard of LCH progression. MAPK pathway alterations were detected in 59 out of 69 cases (86%) ( BRAF V600E mutation: 36%, BRAF N486_P490 deletion: 28%, MAP2K1 mutations: 15%, isolated NRAS Q61 mutations: 4%), while KRAS mutations were virtually absent in PLCH lesions. The BRAF V600E mutation was not associated with LCH presentation at diagnosis, including smoking status and lung function, in PLCH patients. BRAF V600E status did not influence the risk of LCH progression over time. Thus, MAPK alterations are present in most lesions from adult LCH patients, particularly in PLCH. Unlike reports in paediatric LCH, BRAF V600E genotyping did not provide additional information on disease outcome. The search for alterations involved in the MAPK pathway, including BRAF deletions, is useful for guiding targeted treatment in selected patients with refractory progressive LCH. MAPK alterations are present in most lesions from adult pulmonary LCH patients. In patients with refractory progressive disease, the identification of these alterations, including BRAF deletions, is important to guide the choice of targeted treatment. http://bit.ly/2Qoknsn